STRATEGIES FOR THE FORMATION OF COMPENSATORY COMPETENCE AMONG STUDENTS LEARNING GERMAN AS A SECOND FOREIGN LANGUAGE (International journal of artificial intelligence, 2026)
This article addresses the critical need for developing compensatory competence among students learning German as a second foreign language. It aims to identify and analyze effective pedagogical strategies designed to facilitate the formation of this crucial skill. The research explores various approaches, including metacognitive strategies, communicative exercises, and the use of authentic materials, tailored to overcome linguistic gaps and foster independent language use. By implementing these strategies, learners can enhance their ability to maintain communication despite limited linguistic resources, thereby improving overall language proficiency and confidence. The findings offer valuable insights for educators and curriculum developers in optimizing second foreign language instruction.